2000
DOI: 10.1016/s0735-1097(00)00688-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and clinical significance of pseudothrombocytopenia during abciximab therapy

Abstract: Pseudothrombocytopenia is the cause of more than one third (36.3%) of low platelet counts in patients undergoing coronary interventions who are treated with abciximab. This study demonstrates that pseudothrombocytopenia is a benign laboratory condition that does not increase bleeding, stroke, transfusion requirements or the need for repeat revascularization. It is important to recognize pseudothrombocytopenia so that the beneficial effects of abciximab are not lost by premature termination of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 21 publications
1
65
0
2
Order By: Relevance
“…"Thrombocytopenia" following abciximab treatment can be artifactual (pseudothrombocytopenia), being the result of clumping of platelets in blood collected in ethylenediaminetetraacetic acid anticoagulant through mechanisms not yet fully understood. 28,29 However, pseudothrombocytopenia rarely leads to platelet counts as low as the ones observed in the subjects of this report. Moreover, it is not generally associated with bleeding, whereas the patients we studied had extensive petechial hemorrhages (all patients), bleeding from venipuncture sites (patients no.…”
Section: Discussionmentioning
confidence: 48%
“…"Thrombocytopenia" following abciximab treatment can be artifactual (pseudothrombocytopenia), being the result of clumping of platelets in blood collected in ethylenediaminetetraacetic acid anticoagulant through mechanisms not yet fully understood. 28,29 However, pseudothrombocytopenia rarely leads to platelet counts as low as the ones observed in the subjects of this report. Moreover, it is not generally associated with bleeding, whereas the patients we studied had extensive petechial hemorrhages (all patients), bleeding from venipuncture sites (patients no.…”
Section: Discussionmentioning
confidence: 48%
“…1,[3][4][5][6][7][8][9][10][11][12] However, the present study demonstrates by a number of independent methods that neither abciximab (the GP IIb/IIIa antagonist primarily studied by Peter et al), 2 nor tirofiban, nor eptifibatide (the other two FDA-approved GP IIb/IIIa antagonists), nor SC-54701 (the active metabolite of the oral GP IIb/IIIa antagonist xemilofiban) induce stable fibrinogen binding or platelet aggregation under physiological conditions. Furthermore, the findings of Peter et al 2 in experiments with unfixed platelets are probably accounted for by artifactual thrombin generation.…”
Section: Discussionmentioning
confidence: 91%
“…However, the apparently paradoxical results of Peter et al 2 1,[3][4][5]7,9,11,12 (2) the recently reported disappointing results of abciximab in the GUSTO-IV trial of unstable angina, 1 and, (3) abciximab-induced pseudothrombocytopenia. 10 Therefore, in the present study, we reexamined the findings of Peter et al 2 by using a number of independent methods.…”
mentioning
confidence: 98%
“…prednisone 1-2 mg/kg/day for 2-4 agulants, by platelet clumping on a blood smear weeks) may be administered as the diagnosis may be made from anticoagulated blood or by obtaining a difficult to distinguish from idiopathic thrombonormal platelet count on a blood smear made from cytopenic purpura in which corticosteroids are of nonanticoagulated blood. [8] proven benefit. [5,6,75] For the same reason, intrave-…”
Section: General Laboratory Investigationmentioning
confidence: 99%
“…(EDTA) instead of citrate. [8] However, pseuIn table I these 108 articles are categorised by dothrombocytopenia may also occur in anticoagu-type of publication. lants such as heparin and citrate.…”
mentioning
confidence: 99%